Isolation and partial characterization of a monoclonal antibody to the Rous sarcoma virus transforming protein pp60src. - Parsons, S J (J Virol, 1983)
Transformation of cells by Rous sarcoma virus is mediated by the product of the viral src gene, pp60src. A hybridoma cell line producing an immunoglobulin G3 antibody to pp60src was isolated after lymph node cells from immune mice were fused with mouse myeloma cells (P3-NS1-1). Mice were immunized with p60src purified from Escherichia coli cells expressing the src gene product. The monoclonal antibody immunoprecipitated pp60src from Rous sarcoma virus-transformed cells and recognized an antigenic determinant located in the amino-terminal third of the pp60src protein. IMAGES: